2023
DOI: 10.1002/ecy.4039
|View full text |Cite
|
Sign up to set email alerts
|

Wind and small mammals are complementary fungal dispersers

Abstract: Spore morphotypes detected in spore traps. Black bar represents approx. 10µm in length. Numbers in upper right denote assigned morphotype identification number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…As for seedlings in vitro, a large share of in situ adult mycobiota is not explained by seeds or bulk soil. Contrary to the in vitro experiment, sources of contaminations in situ may be more diverse, including fungi dispersed by wind and small mammals (Borgmann-Winter et al, 2023;Zhou et al, 2021), or even plant debris from the litter (Christian et al, 2017). Though fungi may be transmitted by wind (e.g., spores), the low density of plant individuals (in particular H. salicornicum individuals; fertility islands hypothesis) may limit their dispersion and therefore favour the withholding of verticallytransmitted fungi in H. salicornicum leaves, while the mycobiota of belowground tissues are more likely to be influenced by the environment (horizontal transmission).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for seedlings in vitro, a large share of in situ adult mycobiota is not explained by seeds or bulk soil. Contrary to the in vitro experiment, sources of contaminations in situ may be more diverse, including fungi dispersed by wind and small mammals (Borgmann-Winter et al, 2023;Zhou et al, 2021), or even plant debris from the litter (Christian et al, 2017). Though fungi may be transmitted by wind (e.g., spores), the low density of plant individuals (in particular H. salicornicum individuals; fertility islands hypothesis) may limit their dispersion and therefore favour the withholding of verticallytransmitted fungi in H. salicornicum leaves, while the mycobiota of belowground tissues are more likely to be influenced by the environment (horizontal transmission).…”
Section: Discussionmentioning
confidence: 99%
“…As for seedlings in vitro, a large share of in situ adult mycobiota is not explained by seeds or bulk soil. Contrary to the in vitro experiment, sources of contaminations in situ may be more diverse, including fungi dispersed by wind and small mammals (Borgmann‐Winter et al, 2023 ; Zhou et al, 2021 ), or even plant debris from the litter (Christian et al, 2017 ). Though fungi may be transmitted by wind (e.g., spores), the low density of plant individuals (in particular H .…”
Section: Discussionmentioning
confidence: 99%
“…Within animal and plant studies, biotic mechanisms include attraction (e.g., pollinators, dispersers, and mating partners), aposematism and mimicry (e.g., repellence of consumers), camouflage (e.g., avoidance of consumers) (e.g., outlined in Caro, 2017), and antimicrobial activities (Cordero and Casadevall, 2017). First, fungus-animal interactions are frequent, including the utilization of fruit bodies as a food source by mammals and slugs, as a breeding ground for beetles and flies, or simply as a resting site for flying insects (Elliott et al, 2022;Borgmann-Winter et al, 2023). Attraction might play a role in dispersing sexual spores produced in the fruit body.…”
Section: Biotic Factorsmentioning
confidence: 99%
“…Attraction might play a role in dispersing sexual spores produced in the fruit body. Many studies have indeed suggested that animals may contribute to spore dispersal likely on small spatial scales (Guevara and Dirzo, 1999;Lilleskov and Bruns, 2005;Seibold et al, 2019;Elliott et al, 2022;Borgmann-Winter et al, 2023); however, wind dispersal is relevant for both short-and long-distance dispersal (Finlay and Clarke, 1999;Hallenberg and Kuffer, 2001;Galante et al, 2011;Golan and Pringle, 2017). Furthermore, the attraction could also signal profitability, similar to the color change of plant fruits when ripe (Sinnott-Armstrong et al, 2021).…”
Section: Biotic Factorsmentioning
confidence: 99%
“…Thus, it is not surprising that resource availability is one of the predominant mechanisms invoked to understand the assembly of AM fungi in plant roots from a local species pool. Dispersal factors, along with AM fungal preferences for certain soil characteristics and certain plant hosts, are all important in shaping the local species pool of AM fungi [ 7 , 8 ], and ultimately the assembly of AM fungi in plant roots [ 9 ]. What is surprising, however, is the limited attention given to understanding how antagonistic interactions, such as herbivory or pathogen infection, determine the outcome of resource availability on AM fungal community assembly.…”
mentioning
confidence: 99%